Congenital amusia: A group study of adults afflicted with a music-specific disorder - AYOTTE, Julie; PERETZ, Isabelle; HYDE, Krista (Brain (London, England : 1878), 2002)
The condition of congenital amusia, commonly known as tone-deafness, has been described for more than a century, but has received little empirical attention. In the present study, a research effort has been made to document in detail the behavioural manifestations of congenital amusia. A group of 11 adults, fitting stringent criteria of musical disabilities, were examined in a series of tests originally designed to assess the presence and specificity of musical disorders in brain-damaged patients. The results show that congenital amusia is related to severe deficiencies in processing pitch variations. The deficit extends to impairments in music memory and recognition as well as in singing and the ability to tap in time to music. Interestingly, the disorder appears specific to the musical domain. Congenital amusical individuals process and recognize speech, including speech prosody, common environmental sounds and human voices, as well as control subjects. Thus, the present study convincingly demonstrates the existence of congenital amusia as a new class of learning disabilities that affect musical abilities.